The Estimation of Cortical Activity for Brain-Computer Interface: Applications in a Domotic Context. (30th August 2007) - Babiloni, F.; Cincotti, F.; Marciani, M.; Salinari, S.; Astolfi, L.; Tocci, A.; Aloise, F.; Fallani, F. De Vico; Bufalari, S.; Mattia, D.
Abstract : In order to analyze whether the use of the cortical activity, estimated from noninvasive EEG recordings, could be useful to detect mental states related to the imagination of limb movements, we estimate cortical activity from high-resolution EEG recordings in a group of healthy subjects by using realistic head models. Such cortical activity was estimated in region of interest associated with the subject's Brodmann areas by using a depth-weighted minimum norm technique. Results showed that the use of the cortical-estimated activity instead of the unprocessed EEG improves the recognition of the mental states associated to the limb movement imagination in the group of normal subjects. The BCI methodology presented here has been used in a group of disabled patients in order to give them a suitable control of several electronic devices disposed in a three-room environment devoted to the neurorehabilitation. Four of six patients were able to control several electronic devices in this domotic context with the BCI system.